Dictionary of video and television technology - Jack, Keith, 1955-; Tsatsulin, Vladimir, 1937-; Elsevier Science Publishers (Amsterdam ; Boston : Newnes Press, 2002)
This up-to-date reference is the most complete dictionary covering this fast-paced field. It contains virtually all the terminology commonly used in modern global video and television technology, with thorough definitions aimed at the engineering level. It covers all international video standards, digital and analog video signals, data compression, video conferencing, encoding/decoding--indeed, every term associated with video/television technology. Compiled by two internationally recognized video/television experts, this dictionary promises to become a standard reference. *Provides comprehensive and up-to-date information, including coverage of test and measurement procedures *Electronic version of the book accompanies text *Authors are both heavily experienced engineers and authors whose previous works are respected world wide.
Keywords: Television -- Dictionaries; Digital video -- Dictionaries; Electronic books; Dictionaries